2019
DOI: 10.1016/j.chembiol.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Strategy for Protease Substrate Profiling

Abstract: Highlights d A 2PCA-biotin probe enables chemical enrichment of protease substrates (CHOPS) d CHOPS rapidly identifies DPP substrates with a gel-based readout d DPP9 preferentially cleaves short peptides, not whole proteins (e.g., Nlrp1b) d CHOPS enables unbiased protease substrate profiling with quantitative proteomics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 47 publications
2
74
0
Order By: Relevance
“…2c ). Consistent with previous studies 8 , 9 , 25 , N-terminal sequencing indicated that the seven non-structured, N-terminal residues of the UPA N-loop were not cleaved by DPP9 (Extended Data Fig. 5a ).…”
Section: Specific Interaction Between Rnlrp1 and Rdpp9supporting
confidence: 90%
“…2c ). Consistent with previous studies 8 , 9 , 25 , N-terminal sequencing indicated that the seven non-structured, N-terminal residues of the UPA N-loop were not cleaved by DPP9 (Extended Data Fig. 5a ).…”
Section: Specific Interaction Between Rnlrp1 and Rdpp9supporting
confidence: 90%
“…1822 DPP8/9 are highly related intracellular serine dipeptidyl peptidases that cleave N-terminal dipeptides from polypeptide substrates. 23,24 DPP8/9 inhibitors, like LF, induce the proteasome-mediated degradation of the inflammasome N-terminal fragments, but the mechanistic basis of this response remains unknown. 13,20 Zhong and co-workers recently reported that DPP9 directly binds to both human NLRP1 and CARD8 and suggested that the DPP9 protein itself, in addition to its catalytic activity, may play a role in inhibiting NLRP1.…”
mentioning
confidence: 99%
“…63,64 Interestingly, the neo-N-terminus of the NLRP1 C-terminal fragment is NH 2 -Ser-Pro, raising the possibility that DPP8/9 directly cleaves NLRP1 itself to restrain inflammasome assembly. However, a study using Chemical Enrichment of Protease Substrates (CHOPS) found that the mNLRP1B allele 1 C-terminal fragment is not a direct DPP8/9 substrate, 65 and immunoprecipitation-mass spectrometry (IP-MS) experiments failed to identify an N-terminal peptide consistent with DPP8/9 cleavage of hNLRP1. 62 Moreover, the N-terminal sequence of CARD8's neo-C-terminal fragment is NH 2 -Ser-Leu, which is not a preferred DPP8/9 substrate.…”
Section: The D Ipep Tidyl Pep Tida S E S 8 and 9 (D Pp8/9)mentioning
confidence: 99%
“…It is possible that some, as yet unknown, DPP8/9 substrate(s) regulate NLRP1 and CARD8 activation. 56,62 Intriguingly, DPP9 substrate profiling studies using terminal amine isotopic labelling of substrates (TAILS) in SKOV3 cells 66 and CHOPS in THP-1 cells 65 identified very few potential protein substrates. Instead, CHOPS analysis indicated that DPP8/9 preferentially cleaved after proline residues in unstructured peptides, rather than globular proteins.…”
Section: The D Ipep Tidyl Pep Tida S E S 8 and 9 (D Pp8/9)mentioning
confidence: 99%